Comparative transcriptomic analysis of rabbit interscapular brown adipose tissue whitening under physiological conditions. (31st December 2022) - Li, Lei; Wan, Qian; Long, Qiaoyun; Nie, Tao; Zhao, Shiting; Mao, Liufeng; Cheng, Chuanli; Zou, Chao; Loomes, Kerry; Xu, Aimin; Lai, Liangxue; Liu, Xin; et al.
ABSTRACT: Interscapular brown adipose tissue (iBAT) of both rabbits and humans exhibits a similar whitening phenomenon under physiological conditions. However, a detailed characterization of iBAT whitening in them is still lacking. Here, we chose rabbits as a model to gain a better understanding of the molecular signature changes during the whitening process of iBAT by transcriptomic analysis of rabbit iBAT at day 1, day 14, 1 month and 4 months after birth. We applied non-invasive MRI imaging to monitor the whitening process and correlated these changes with analysis of morphological, histological and molecular features. Principal component analysis (PCA) of differentially expressed genes delineated three major phases for the whitening process as Brown, Transition and Whitened BAT phases. RNA-sequencing data revealed that whitening of iBAT was an orchestrated process where multiple types of cells and tissues participated in a variety of physiological processes including neovascularization, formation of new nervous networks and immune regulation. Several key metabolic and signalling pathways contributed to whitening of iBAT, and immune cells and immune regulation appeared to play an overarching role.